2012
DOI: 10.4103/0019-5049.96308
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with intravenous granisetron to alleviate pain on propofol injection: A double-blind, randomized, controlled trial

Abstract: Background:Propofol is one of the widely used intravenous (i.v.) anaesthetics, although pain on injection still remains a considerable concern for the anaesthesiologists. A number of techniques has been tried to minimize propofol-induced pain with variable results. Recently, a 5-HT3 antagonist, ondansetron pre-treatment, has been shown to reduce propofol-induced pain. The aim of our randomized, placebo-controlled, double-blinded study was to determine whether pre-treatment with intravenous granisetron, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…This was similar to the way the study conducted by to R.A. Johnson et al 1990 [19] , S.P. Ambesh et al 1999 [8] , Ahmed etal [71] .…”
Section: Discussionsupporting
confidence: 71%
“…This was similar to the way the study conducted by to R.A. Johnson et al 1990 [19] , S.P. Ambesh et al 1999 [8] , Ahmed etal [71] .…”
Section: Discussionsupporting
confidence: 71%
“…[14] The dose of granisetron used in our study was 2ml (1mg/ml) as this dose was considered to be effective as in previous study. [1] In our study, distribution of age ranged between 18-50 yrs with the mean age of lignocaine group being 38yrs and for granisetron group being 40 yrs. Majority of patients in both Licensed Under Creative Commons Attribution CC BY groups were males, 64% in lignocaine group and 52% in granisetron group.…”
Section: Discussionmentioning
confidence: 99%
“…Pain on injection of anaesthetic is an important cause of patient dissatisfaction and is a recognised adverse effect of propofol. [1] The reported incidence of pain on injection of propofol varies between 28% and 90% in adults if a vein on dorsum of the hand is used. [2] It is known to cause severe, sharp, stinging or burning pain on injection that can be distressing to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer patients in the granisetron group experienced severe pain (2.5% vs. 37.5%; P<0.05). (Ahmed A et al, 2012) 42 In a study by Ambesh et al on effect of ondensetron in injection of propofol, the overall incidence of pain in the saline group was 55%, compared with 25% in the ondensetron group (p=0.05). [Ambesh SP et al, 1999] 1 Singh DK et al, reported that granisetron reduced the incidence of propofol injection pain to 24% at 5 seconds, 24% at 10 seconds, 40% at 15 seconds and 40% at 20 seconds in comparison to the control group, whereas placebo had an incidence of 80% at 5 seconds, 84% at 10 seconds, 88% at 15 seconds and 88% at 20 seconds and showed statistical significance.…”
Section: Granisetronmentioning
confidence: 99%